2008
DOI: 10.1002/lsm.20621
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea treatment using the new‐generation, high‐energy, 595 nm, long pulse‐duration pulsed‐dye laser

Abstract: The high-energy, long pulse-duration pulsed-dye laser improves rosacea with a very favorable safety profile, and less purpura than resulted from earlier generation pulsed-dye lasers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 29 publications
1
58
0
6
Order By: Relevance
“…PDL'ye bağlı yan etkiler göz önüne alınarak yeni jenerasyon uzun atımlı PDL tedavisi uygulanan rozase hastalarında tedavi sonunda lezyonlarda anlamlı oranda değişiklik saptanmıştır. Tek seans uygulama sonrasında bile lezyonların %75'inde fark edilir bir iyileşme (%25'den fazla) olduğunu öne sürülmüştür [14][15][16][17] . Literatürde yapılan PDL çalışmalarında lazer tedavisinin rozasenin eritem ve telanjiyektazilerine orta derecede etki gösterdiği görülmektedir.…”
Section: Discussionunclassified
“…PDL'ye bağlı yan etkiler göz önüne alınarak yeni jenerasyon uzun atımlı PDL tedavisi uygulanan rozase hastalarında tedavi sonunda lezyonlarda anlamlı oranda değişiklik saptanmıştır. Tek seans uygulama sonrasında bile lezyonların %75'inde fark edilir bir iyileşme (%25'den fazla) olduğunu öne sürülmüştür [14][15][16][17] . Literatürde yapılan PDL çalışmalarında lazer tedavisinin rozasenin eritem ve telanjiyektazilerine orta derecede etki gösterdiği görülmektedir.…”
Section: Discussionunclassified
“…Women are affected more than men. According to many research studies, long-pulsed 595 nm PDL constitutes an effective method for the treatment of this condition, as well as the associated erythema and telangiectasia, with minimal adverse events and no long-term complications [63,64] . In one study, long-pulsed 595 nm PDL was used for the treatment of 20 patients with rosacea.…”
Section: Rosaceamentioning
confidence: 99%
“…A mean score of 1.4 was observed at the end of the treatment, showing a statistically significant reduction. The investigators concluded that this particular type of laser has very good results in the treatment of rosacea, while its safety profile is as favourable as the PDLs of older technology [63] . Similar were the results in another study, where LPDL was used for the treatment of rosacea-associated telangiectasia and no significant purpura reaction was observed after treatment [65] .…”
Section: Rosaceamentioning
confidence: 99%
“…1,2 The five subtypes of rosacea, according to the modified National Rosacea Society classification system, include erythematotelangiectatic, papulopustular, phymatous, ocular, and mixed subtypes. [3][4][5] Among Koreans with localized nasal rosacea, erythematotelangiectatic rosacea is the most common subtype, followed by papulopustular rosacea.…”
Section: Introductionmentioning
confidence: 99%